Microporous polycarbazole frameworks with large conjugated π systems for cyclohexane separation from cyclohexane-containing mixtures. (23rd November 2021) - Chen, Liangji; Zhang, Hao; Ye, Yingxiang; Yuan, Zhen; Wang, Jiaqi; Yang, Yisi; Lin, Si; Xiang, Fahui; Xiang, Shengchang; Zhang, Zhangjing
Abstract : Two microporous polycarbazole frameworks with large conjugated π systems were constructed for cyclohexane separation from cyclohexane-containing mixtures. Abstract : The separation of cyclohexane from benzene/cyclohexane and cyclohexene/cyclohexane is one of the most important challenges in the chemical industry. Adsorption separation based on porous materials with aromatic backbones and abundant micropores has been a highly anticipated technology. Herein, two novel microporous polycarbazole frameworks, namely, FJU-P6 and FJU-P7, based on two building monomers of carbazole derivatives (BCz and DCzPh ) with large conjugated π systems, were successfully designed and synthesized. The two polymers exhibited both high Brunauer–Emmett–Teller (BET) specific surface areas and microporosity values (1066 m 2 g −1 and 45.8% for FJU-P6 ; 1425 m 2 g −1 and 36.1% for FJU-P7 ). Moreover, obvious adsorption differences for C6 vapors (mainly benzene, cyclohexene and cyclohexane) were observed in FJU-P6 and FJU-P7, and the order of adsorption capacity follows benzene > cyclohexene > cyclohexane. Benzene/cyclohexane selectivity (13.87) and cyclohexene/cyclohexane selectivity (1.60) were evaluated using ideal adsorbed solution theory (IAST), which demonstrates that the resultant polymers have potential applications in the selective separation of cyclohexane from cyclohexane-containing mixtures. Calculation of the binding energy shows that C–H⋯π interactions between guests and skeletons play a dominant role in the separation of C6 vapors. This work provides insight into the design of microporous conjugated polymers for the challenging separation of C6 vapors.